Technical assistance for institutional capacity building: the transferability of administrative structures and practices - Desai, Uday; Snavely, Keith (2007)
The US government has been actively engaged for the last 15 years in foreign assistance programs for building democratic governance institutions and enhancing overall government capacity in the former Soviet bloc countries. Transfers of public policies, administrative structures and management practices from one country to another are problematic. In this article we suggest that there are some fundamental constraints inherent in the framework of cross-national transfers. It identifies two major transferability challenges: (1) feasibility of transfer and (2) appropriateness of transfer. This article discusses three institution building programs of short duration (three to five years), whose broad purposes were institutional and professional capacity building. Many powerful forces, domestic and international, shape the likelihood of democratic consolidation in the transitional democracies. While fundamental questions about the transferability of institutional norms and structures from one country to another remain, our experiences indicate that thoughtful and flexible implementation strategies are likely to increase the chances that softy technology transfer projects will contribute to building institutional capacity. A great degree of uncertainty, nevertheless, will always remain in determining the long-term impacts of foreign technical assistance programs for transfer of institutional norms and structures. - Reproduced.
Keywords: Administrative structure